Prospective Surveillance and Rapid Whole-Genome Sequencing Detects Two Unsuspected Outbreaks of Carbapenemase-Producing Klebsiella pneumoniae in a UK Teaching Hospital. (4th October 2017) - Torok, Estee; Brodrick, Hayley; Khokhar, Fahad; Blane, Beth; Polgarova, Petra; Brown, Joanne; Enoch, David; Brown, Nicholas; Summers, Charlotte; Preller, Jacobus; Thomson, Nick; Dougan, Gordon; et al.
Abstract: Background: The increasing incidence of carbapenemase-producing Enterobacteriaceae (CPE) is a global health concern, as treatment options are extremely limited. The prevalence of CPE in UK hospitals is unknown, as national screening guidelines only recommend screening in patients considered to be at high-risk of CPE. Patients in intensive care units (ICU) are at high-risk of healthcare-associated infections caused by multidrug-resistant organisms (MDRO). Methods: We conducted a six-month prospective surveillance study to determine the prevalence of MDRO in a UK teaching hospital ICU. Between June and December 2016, all adult patients admitted to ICU were screened for MDRO on admission, on discharge, and weekly during their ICU stay. Surveillance samples included stool or rectal swabs, urine, sputum or tracheal aspirates, and wound swabs (if wounds were present). Isolates were characterized phenotypically before undergoing whole-genome sequencing (WGS), epidemiological, and phylogenetic analyses. Results: During the first week of the study we identified stool carriage of a multidrug-resistant Klebsiella pneumoniae strain in two patients neither of whom had recognized risk factors for CPE. Both isolates were resistant to all antibiotics tested, apart from colistin, and were PCR-positive for the bla NDM-1 gene. Enhanced surveillance by the infection control team identified four additional patients in several wards who had stool carriage ( n  = 3) or bloodstream infection ( n  = 1) with a bla NDM-1 K. pneumoniae isolate . Epidemiological links were identified between these six patients. Five months later, a second outbreak of multidrug-resistant K. pneumoniae was detected, involving stool carriage by four patients on two different wards. Environmental screening identified environmental contamination with multidrug-resistant K. pneumoniae on one ward. DNA sequence analysis confirmed that a novel bla NDM-1 K. pneumoniae lineage (ST78) was responsible for both outbreaks in the hospital. Conclusion: We identified two unsuspected bla NDM-1 K. pneumoniae outbreaks in patients with no recognized risk factors for CPE. This highlights the importance of prospective surveillance for MDRO in high-risk settings, such as ICUs, and supports the use of rapid WGS to support outbreak investigations in real-time. Disclosures: All authors: No reported disclosures.